Tomato Inoculation With a Non-pathogenic Strain of Fusarium oxysporum Enhances Pest Control by Changing the Feeding Preference of an Omnivorous Predator - Eschweiler, Julia; van Holstein-Saj, Renata; Kruidhof, H. Marjolein; Schouten, Alexander; Messelink, Gerben J. (Frontiers in Ecology and Evolution, 2019)
Mirid predators, a special group of plant-feeding omnivorous predators, have become important biological control agents for pest control in greenhouse cropping systems. Their efficacy and behavior may potentially be affected by microorganisms that induce plant defenses or change plant quality. Here we studied the interaction between a root restricted endophytic non-pathogenic strain of Fusarium oxysporum (Fo162) in tomato plants, the greenhouse whitefly Trialeurodes vaporariorum (Westwood) and the plant-feeding mirid predator Macrolophus pygmaeus (Rambur). In the absence of prey, inoculation of tomato plants with the Fo162 endophyte significantly reduced the reproduction of M. pygmaeus compared to plants without the endophyte. In contrast, the population growth of M. pygmaeus was not affected by the Fo162 endophyte in the presence of whiteflies. Moreover, the combination of the predator and endophyte resulted in lower whitefly densities than the predator alone. Whitefly population development was not different between endophyte-inoculated and untreated plants. Thus, endophyte inoculation of tomato plants seems to shift the feeding preference of this omnivorous predator from plant consumption towards relatively more prey consumption, resulting in enhanced suppression of the herbivore. Moreover, the negative effect of the endophyte on M. pygmaeus reproduction could easily be eliminated by providing decapsulated cysts of Artemia franciscana Kellogg as a supplemental food source. Together, this suggests an overall net positive effect of the Fo162 endophyte on a preventive biological control strategy in tomato using M. pygmaeus. Besides the enhanced whitefly control, endophyte-inoculation of tomato plants both with or without the predator also resulted in a higher yield and a reduced number of fruits with blossom-end rot, a disorder caused by limitations in uptake and transport of calcium to the fruits. This suggests that the Fo162 endophyte is also involved in the acquisition of essential nutrients for the benefit for the plant. Since both the Fo162 endophyte and the predator M. pygmaeus can induce plant defense, further studies need to elucidate the exact mechanisms that occur when both organisms are present. Our findings confirm the importance of studying endophytes and induced plant responses in a multi-trophic context with herbivores and their natural enemies.